KONSTRUKSI HUKUM HAKIM AGUNG DALAM MEMUTUS SENGKETA PAJAK PERTAMBAHAN NILAI PERUSAHAAN BATU BARA (Studi Kasus Putusan Mahkamah Agung Nomor : 36/B/PK/PJK/2016) - Agus Suharsono (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2022)
This study aims to analyze and synthesize the legal construction of the Supreme Court justices in deciding the value added tax dispute of coal companies so that they can be used as legal considerations for tax authorities and taxpayers who are in the coal mining sector in fulfilling their tax obligations. The method used is doctrinal research which analyzes primary and secondary legal sources. The results of the study show that the construction of the Supreme Court judge in deciding the value added tax dispute for coal companies is not only guided by written regulations and documents, but also explores, follows, and understands the legal values and sense of justice that live in the coal business world. The Supreme Court judge is of the opinion that the Certificate of Origin is not the basis for calculating the volume of coal delivery, income from debt payments is not an object of value added tax, foreign exchange income is not an object of value added, and sales of assets which according to their original purpose were not traded by coal mining companies are not value added tax object.